VNF lifecycle security management measures in NFV - Jian SU; Ziyu XIAO (Dianxin kexue)
The dynamic feature of NFV demands that security technologies,policies,processes and practices were embedded in the genetic fabric of VNF.The VNF security management lifecycle represented the security processes spanning from VNF platform guidance,to VNF instantiation,operation and retirement.It was intended to represent a process view of VNF security and process guidance.